The Problem of the ‘Phenomenological World’ in Husserl’s Philosophy - Rolewski, Jarosław (Folia Philosophica, 2023)
This paper discusses the notion of the ‘phenomenological world’ and the problems it generates in the ‘hard’ paradigm of Husserl’s phenomenology, such as the lack of universality and intersubjectivity of this world, its closure and privacy, and its being only the personal world of a subject. Also, an attempt was made to show some of the sources of this problematic situation and the impossibility of solving it in a fundamentalist paradigm. It is only in the last period of the development of Husserl’s phenomenology (the so-called period of the Crisis) that these problems find their satisfactory solution.